2018
DOI: 10.1038/s41598-018-29062-w
|View full text |Cite
|
Sign up to set email alerts
|

Buparlisib is a brain penetrable pan-PI3K inhibitor

Abstract: Characterization of the genomic landscapes of intracranial tumours has revealed a clear role for the PI3K-AKT-mTOR pathway in tumorigenesis and tumour maintenance of these malignancies, making phosphatidylinositol 3-kinase (PI3K) inhibition a promising therapeutic strategy for these tumours. Buparlisib is a novel pan-PI3K inhibitor that is currently in clinical development for various cancers, including primary and secondary brain tumours. Importantly however, earlier studies have revealed that sufficient brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Notably, any grade anxiety and any grade depression were reported in 18% of patients. Buparlisib is one of the PI3K inhibitors with highest blood-brain barrier penetration [ 23 ]. However, the physiopathology of mood disorders associated with pan-PI3K inhibitors has not been well characterized, and it remains unclear whether the higher incidence of neuropsychiatric effects observed with buparlisib compared to isoform-selective PI3K inhibitors is due to its elevated CNS penetration or to other pharmacokinetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, any grade anxiety and any grade depression were reported in 18% of patients. Buparlisib is one of the PI3K inhibitors with highest blood-brain barrier penetration [ 23 ]. However, the physiopathology of mood disorders associated with pan-PI3K inhibitors has not been well characterized, and it remains unclear whether the higher incidence of neuropsychiatric effects observed with buparlisib compared to isoform-selective PI3K inhibitors is due to its elevated CNS penetration or to other pharmacokinetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results showed that the overall response rate in DLBCL was 12% [61] . Another study showed that buparlisib had excellent brain penetration regardless of the influence of the blood-brain barrier, complete oral bioavailability, and efficient intracranial target inhibition at clinically achievable plasma concentrations [62] . These studies provide information that will aid the development of targeted therapeutic strategies for PCNSL patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Buparlisib has also been shown to cross the blood-brain barrier, accumulate in the brain tissue of non-tumour-bearing rats, and efficiently downregulate tissue phospho-S6 and phospho-AKT. 20 Buparlisib has also shown preclinical efficacy in various PI3K pathway-hyperactivated cancer models, including GBM. [21][22][23][24] Here, we report the maximum tolerated dose (MTD) and the recommended phase II dose (RP2D) of buparlisib in combination with carboplatin or lomustine and the safety and preliminary antitumour activity of these combinations in patients with rGBM.…”
Section: Key Questionsmentioning
confidence: 99%
“… 19 Buparlisib has also been shown to cross the blood–brain barrier, accumulate in the brain tissue of non-tumour-bearing rats, and efficiently downregulate tissue phospho-S6 and phospho-AKT. 20 Buparlisib has also shown preclinical efficacy in various PI3K pathway-hyperactivated cancer models, including GBM. 21–24 …”
Section: Introductionmentioning
confidence: 99%